Exploitation Of Locally Available Organic Wastes For Rearing Black Soldier Fly (Hermetia Illucens) Larvae As A Potential Protein Ingredient For Poultry And Fish Feeds In Uganda - Onen, Hudson; Odong, Robinson; Chemurot, Moses (Journal of Biology and Nature, 2019)
The animal industry especially aquaculture and poultry sectors contribute greatly to the livelihoods of households in sub-Saharan African countries. The ongoing depletion of fish stocks used as protein source requires substitution with alternative animal sources, e.g. black soldier fly (BSF) larvae, Hermetia illucens. Hence, this study assessed the growth performance of BSF larvae reared on locally and readily available organic wastes. Five organic waste types/substrates (cattle and swine dropping, chicken house rearing waste, decomposing avocado and millet brew wastes) were tested. Randomly selected third larval instar of BSF from each rearing substrate were measured: girth (in cm), length (in cm) and weight (in grams) using a vernier calliper and a weighing scale respectively. The findings indicate that in the 12 weeks period, millet brew wastes produced larvae with the widest girth, longest length and were heaviest, followed by decomposing avocado, waste from chicken rearing house, cattle and swine droppings. In conclusion, the growth performance of BSF larvae was influenced by substrates investigated. We recommend further studies to determine the nutritional composition of BSF larvae raised on each of the substrates investigated in this study.
Keywords: Black soldier fly; feeds; fish; organic waste; poultry